A systematic review of mangrove restoration studies in Southeast Asia: Challenges and opportunities for the United Nation’s Decade on Ecosystem Restoration - Gerona-Daga, Maria Elisa B.; Salmo, Severino G. (Frontiers in Marine Science, 2022)
Mangroves provide valuable ecological and socio-economic services. The importance of mangroves is particularly evident in Southeast (SE) Asia where the most extensive and diverse forests are found. To recover degraded mangroves, several SE Asian countries have implemented restoration programs. However, to date, there has been no systematic and quantitative synthesis on mangrove restoration studies in the region. Here, we provide a bibliometric-based analysis of mangrove restoration to provide understanding on trends and future directions needed to meet biodiversity and restoration targets in the region. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, we analyzed 335 articles (249 articles with ecological attributes; 86 articles with social attributes) published until February 2022 from Scopus and Web of Science databases. Mangrove restoration studies with ecological and social attributes started around the early 1990s mostly from Indonesia, Thailand, Malaysia, Vietnam, and the Philippines. Majority of SE Asian countries have stronger collaboration to western countries rather than within the region. Reasons for restoration vary per country, but mostly were intended to rehabilitate damaged mangroves. Direct planting was the most common restoration method used while hydrological rehabilitation was less practiced. Research on ecological attributes were dominated by biodiversity-related studies focused on flora and fauna, and less on other ecosystem services (e.g., coastal protection, fisheries production, etc.). Studies with social attributes only accounted for <30% of the publications, mostly on topics related to ecological economics. Although mangrove restoration studies are apparent, some thematic restoration foci are needed. We propose priority research topics to help achieve the biodiversity and restoration targets by 2030.